Influence of Solvent Polarity and Conditions on Extraction of Antioxidant, Flavonoids and Phenolic Content from Averrhoa bilimbi - Norlia, Muhamad; Siti Aishah, Muhmed; M. M., Yusoff; Jolius, Gimbun (David Publishing, 2014)
This paper presents the influence of solvent polarity and extraction conditions on the extraction of total flavonoid, total phenolic and antioxidants from Averrhoa bilimbi. The experiment was performed using a different solvent at different extraction conditions, including extraction time (15-240 min), temperature (30-70 °C) and agitation speed (50-300 rpm). Results showed that yields of extraction varies with solvent polarity. Extraction using 50% aqueous methanol gives the highest antioxidant activity and flavonoid content. The highest total flavonoid content (193.3 µg quercetin equivalent/g dry weight), total phenolic content (717.8 µg gallic acid equivalent/g dry weight) and antioxidant activity (77%) was achieved using 50% methanol, at 70 °C and agitation speed of 300 rpm. This work may be useful for obtaining higher bioactive compounds during the extraction process of A. bilimbi.